1999
DOI: 10.1084/jem.189.12.1907
|View full text |Cite
|
Sign up to set email alerts
|

An Invariant T Cell Receptor α Chain Defines a Novel TAP-independent Major Histocompatibility Complex Class Ib–restricted α/β T Cell Subpopulation in Mammals

Abstract: We describe here a new subset of T cells, found in humans, mice, and cattle. These cells bear a canonical T cell receptor (TCR) α chain containing hAV7S2 and AJ33 in humans and the homologous AV19-AJ33 in mice and cattle with a CDR3 of constant length. These T cells are CD4−CD8− double-negative (DN) T cells in the three species and also CD8αα in humans. In humans, their frequency was ∼1/10 in DN, 1/50 in CD8α+, and 1/6,000 in CD4+ lymphocytes, and they display an activated/memory phenotype (CD45RAloCD45RO+). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
731
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 543 publications
(794 citation statements)
references
References 65 publications
36
731
4
Order By: Relevance
“…The MAIT cells were shown early on to be present in the human gut lamina propria,1, 2 to express the gut homing integrin α 4 / β 7 , and have been considered to be preferentially located in mucosal tissue 27. Moreover an important role in gastrointestinal mucosal immunity is suggested by the dependence on commensal gut flora for their development in mice 2, 16.…”
Section: Observations From Specific Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAIT cells were shown early on to be present in the human gut lamina propria,1, 2 to express the gut homing integrin α 4 / β 7 , and have been considered to be preferentially located in mucosal tissue 27. Moreover an important role in gastrointestinal mucosal immunity is suggested by the dependence on commensal gut flora for their development in mice 2, 16.…”
Section: Observations From Specific Diseasesmentioning
confidence: 99%
“…Mucosal‐associated invariant T (MAIT) cells are a subset of innate‐like T lymphocytes first described in 1999,1 which are abundant in humans and can rapidly express a range of pro‐inflammatory cytokines. Although MAIT cells express an αβ T‐cell receptor (TCR) they differ from conventional T cells in that this receptor has a limited TCR diversity, mostly comprising a semi‐invariant TCR‐ α chain associated with a limited repertoire of TCR‐ β chains (Box 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paraformaldehyde fixed healthy human jejunal tissue biopsies Va7.2 positive cells are located in the LP at the base of the villi, and less commonly in the villus tip, and in the IEL compartment [43]. Numbers of MAITs in wild type mice are far lower than in humans and are mainly confined to the intestinal LP and lymph nodes (they were not detected in the liver, bone marrow or spleen in mice) [10,49]. Although initial research demonstrated significant numbers of MAIT cells at mucosal sites, recently, significant accumulation of MAITs was also revealed in the human liver (up to 45% of hepatic T lymphocytes) [45].…”
Section: Characteristics Of Mait Cellsmentioning
confidence: 96%
“…However, targeting populations of unconventional T cells may represent a highly productive strategy to improve the efficacy of oral vaccines at mucosal surfaces. Mucosal associated invariant T (MAIT) cells are a recently discovered innate populations of unconventional T cells [9,10]. These cells accumulate at mucosal sites, home to mucosal tissue when activated, rapidly produce immunomodulatory cytokines in response to bacterial stimuli, can bridge innate and adaptive immunity, and share common features with the more widely studied invariant Natural Killer T (iNKT) cells, agonists of which have previously been shown to have vaccine adjuvant properties.…”
Section: Mucosal-associated Invariant T (Mait) Cells Are a Recently Dmentioning
confidence: 99%